HUBUNGAN DUKUNGAN KELUARGA DENGAN KEJADIAN ANEMIA DIFISIENSI ZAT BESI PADA IBU HAMIL - Agustina Maunaturrohmah (STRADA : Jurnal Ilmiah Kesehatan, 2013)
The motivation will hope for pregnant’s mother. With motivation of family is a goog will to press anemia on pregnant’sn mother, because anemia is health problem which will not become extinct. This research using to analyze “ Is there any correlation motivation of family with anemia dificience Fe and blooding anemia on pregnant’s motherin Bulujowo village. This research is analytic cross secsionalyty. The population in the research are all of pregnant mother family’s in Bulujowo village using total sampling. The independent variable is the family’s motivation while dependent variable is anemia dificience Fe and blooding anemia on pregnant’s mother. The data collection are using quisioner and hemoglobin’s observation on pregnat’s mother . to analyze the correlation is used by spearmen rankcorrelation using ρ 0,05. The research values shows that presentasion of 83,33% pregnant’s mother between 20-30 years old, 43,33% on trimester I and III, husband education are senior high scool 60%, 76,67% for good motivation, 76,67% normal with Hb >11gr% The volues of statistic tes is using the spearmen rank correlation which gets probability 0,000, which shows that H0 is an acceptable than H1 is acceptable. The conclusion of research is the correlation of family;s motivation with anemia dificience Fe and blooding anemia of pregnant’s mother. I suggest that every pregnant’s mother family in order to always giving motivation to the pregnant’s mother such ad nutrition, pregnant’s check up, affection’s guidance in order to pregnantcy’s process such as giving birth, porturation and bany’s growth become optimum.